Developing Writing Skill Scoring Rubric for Junior Secondary School - Armin, Diah Safithri; Purnomo, Maslathif Dwi; Alvindi, Alvindi (SCOPE: Journal of English Language Teaching, 2024)
This research aims to reveal the development of a writing skill scoring rubric for a Junior Secondary School based on an analysis of teacher needs for a writing skill scoring rubric. This research method uses the ADDIE Research and Development (R & D) research method with limitations of only three stages, namely: 1) Analysis, 2) Design, and 3) Development. The data collection method in this research used interviews and questionnaire validation sheets filled in by evaluation experts and field practitioners. The subjects of this research were seven English teachers from three different junior secondary schools. The results of research product validation by learning evaluation experts concerning content suitability were 96.67%. Then, the validation results for presentation feasibility were 90.62%. Meanwhile, the validity percentage for the linguistic appropriateness aspect was obtained at 96.87%. In addition to these quantitative results, the validator also suggests minor revisions to the appearance and content. In the practicality trial, research subjects were given a questionnaire containing an assessment of the appropriateness of presentation, content, and language appropriateness. Based on the results of the analysis, for the presentation feasibility test, a feasibility percentage of 98.38% was obtained. The analysis results for the content feasibility test showed a feasibility percentage of 98.21%, while for linguistic feasibility, it was 99.1%. Overall, the validation results by learning evaluation experts and practicality tests by field practitioners show that this research's writing skill scoring rubric is valid and practical to use in assessing students' writing skill abilities.